Clinical profile of heart failure in geriatric patients in a tertiary cardiac hospital of Bangladesh - Mahbuba Yesmin; Lutfun Nahar Nizhu; Afroja Alam; Abdullah Al Mamun (Aging and Health Research)
This study included 100 geriatric patients admitted at National Institute of Cardiovascular Diseases (NICVD) in Bangladesh having clinical features of heart failure, possible other information (Framingham Criteria) and increase in natriuretic peptide or echocardiographic findings. It was a single center, cross sectional study. Regarding functional NYHA classification, 14 % presented with class I, 30 % with class II, 35 % presented with class III, 21 % presented with class IV heart failure.Regarding left ventricular ejection fraction (LVEF), heart failure (HF) was classified into the following categories: (1) HF with reduced EF (HFrEF) - 19 %; (2) HF with improved EF (HFmpEF) - 13 %; (3) HF with mildly reduced EF (HFmrEF) - 22 % and (4) HF with preserved EF (HFpEF) - 46 % . 23 % of the study population had iron deficiency anemia and about one-third-patient had associated renal failure (AKI/CKD). This study revealed that a significant geriatric population has unrecognized heart failure (HFpEF).